THE ROLE OF THE ACMEALOGICAL APPROACH IN THE PROFESSIONAL DEVELOPMENT OF AN EDUCATOR - Nazarova Nigora Ravshanovna (Web of Journals Publishing, 2024)
This article addresses the issues of professional characteristics, ways of their development, which are necessary for each educator. In addition, the role of creativity in the Caspian development and formation of an educator, pedagogical skills, the ability to self –manifest in life-activity were considered and illuminated in a separate systematized form based on an acmealogical approach.
Keywords: Acmealogy , pedagogical skill, pedagogical ability. creativity, cognitive system, expressiveness, motivatsia, professional development, cognitive dissonance.